Teaching to Different Learning Styles - James E. Dyer (EDIS)
WC083, a 3-page illustrated fact sheet by James E. Dyer, defines learning styles, types of learning styles (per the Gregorc Style Delineator), and preferred teaching methods and techniques for each style. Includes references. Published by the UF Department of Agricultural Education and Communication, December 2008.